EVALUASI KINERJA LALU LINTAS DI JALAN PROKLAMASI PASCA OPERASIONAL KANTOR PEMERINTAHAN TERPADU KABUPATEN BREBES - Adam Muakhor; Juny Andry Sulistyo; Rinda Karlina Sari (Bajang Institute, 2025)
Changes in land use and transportation networks greatly affect the accessibility of an area. One of the land use changes that occurred in Brebes Regency is the construction of the Brebes Regency Integrated Government Office (KPT) on Jalan Proklamasi. With the construction of the KPT, it will more or less affect the traffic performance on this section of Jalan Proklamasi. This study aims to analyze traffic performance and develop strategy recommendations. The method used in this research is a mixed method research approach, namely the PKJI (Indonesian Road Capacity Guidelines) 2014 analysis method and the Analytical Hierarchy Process (AHP) method. The results showed that the level of service of the proclamation road section on weekdays before KPT operations was categorized B with a degree of saturation or Q / C ratio value of 0.36 and after (post) KPT operations categorized C with a degree of saturation or Q / C ratio value of 0.66. While the level of road service on holidays both before and after KPT operations is still the same category B with a degree of saturation or Q / C ratio value of 0.23 and 0.44, respectively. It can be concluded that there is a decrease in the level of service of the proclamation road section, namely on weekdays before KPT operations with the level of service of Category B road sections and after KPT operations with the level of service of road sections becoming Category C. Based on the Minister of Transportation Regulation Number 96 of 2015 that the level of service of primary collector roads is at least B, it means that this proclamation road after KPT operations has not met the standard level of road service. Strategy recommendations are in the form of road improvements in the form of road widening from 4 meters wide with 2/2 UD road section type to 14 meters wide with 4/2 UD road section type equipped with pedestrian paths (sidewalks), implementing traffic engineering management in the form of planning, regulating, organizing and maintaining and implementing strict implementation related to the implementation of ANDALALIN documents